2014
DOI: 10.5194/hess-18-4543-2014
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of precipitation in a high-mountain region: exploring methods with multi-scale topographic predictors and circulation types

Abstract: Abstract. Statistical models of the relationship between precipitation and topography are key elements for the spatial interpolation of rain-gauge measurements in high-mountain regions. This study investigates several extensions of the classical precipitation-height model in a direct comparison and within two popular interpolation frameworks, namely linear regression and kriging with external drift. The models studied include predictors of topographic height and slope at several spatial scales, a stratificatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 70 publications
1
30
0
Order By: Relevance
“…An important conclusion of this work is that installing high-resolution (hourly or less) precipitation gauges in previously ungauged locations next to the customary, manual rainmeasuring instrument, even for short periods, has tangible benefits in the estimation of long-term precipitation statistics, such as interannual variability and quantiles of annual precipitation with high return periods. This is important because accurate gauge-level precipitation estimates remain vital for the correction of remotely sensed data and in merging different precipitation data types, e.g., weather radar, and satellite (e.g., Xie and Arkin, 1996), as well as for the spatial interpolation of precipitation, especially in areas with complex topography (e.g., Masson and Frei, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…An important conclusion of this work is that installing high-resolution (hourly or less) precipitation gauges in previously ungauged locations next to the customary, manual rainmeasuring instrument, even for short periods, has tangible benefits in the estimation of long-term precipitation statistics, such as interannual variability and quantiles of annual precipitation with high return periods. This is important because accurate gauge-level precipitation estimates remain vital for the correction of remotely sensed data and in merging different precipitation data types, e.g., weather radar, and satellite (e.g., Xie and Arkin, 1996), as well as for the spatial interpolation of precipitation, especially in areas with complex topography (e.g., Masson and Frei, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that kriging with external drift (KED), using altitude as an external variable, provides good results over complex terrains (e.g., Masson and Frei, 2014;Tobin et al, 2011;Ochoa et al, 2014). Block kriging with altitude as an external drift was thus chosen here as our reference interpolation method -note however that other types of kriging interpolators were tested, but a cross-validation evaluation showed KED to be the most efficient of all in our case.…”
Section: Gridded Precipitation From In Situ Datamentioning
confidence: 99%
“…Future developments will focus on increasing the performances in data-sparse regions, e.g., following the recommendations of Masson and Frei (2014) on the use of climatological precipitation fields for the interpolation of daily precipitation. Furthermore, the issue of wind-induced underestimation of solid precipitation will be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we will use E-OBS as a reference dataset to evaluate seNorge2. The conclusions of the work by Masson and Frei (2014) favor the use of statistical interpolation schemes based on a two-step approach, where the background is estimated from the data, such as Kriging with external drift that is rather similar to OI. In addition, they conclude that the inclusion of a single topographic predictor may be sufficient in the interpolation, and they support "the common practice of using a climatological mean field as a background in the interpolation of daily precipitation".…”
Section: Introductionmentioning
confidence: 99%